An Experimental Study of Postoperative Monitoring for Innervated Free Muscle Graft by the Compound Muscle Action Potential in Rabbits - Tan, Soo-Heong; Shigetomi, Mitsunori; Doi, Kazuteru (Journal of Reconstructive Microsurgery, 2012)
This experiment establishes the principles of using the compound muscle action potential (CMAP) as a possible postoperative monitor for free muscle grafts. Twenty rabbits were divided into two groups of ten each to investigate the effects of ischemia on CMAP of the muscles. Rectus femoris model was used and contralateral muscle was used as control. In all muscles total normothermic ischemia of 1.5 hours to mimic the time needed for transfer and inset of the flap was followed by occlusion of the artery in one group and vein in another group after 3 hours. During this ischemia of 1 hour, the CMAP amplitudes decreased and the latencies were prolonged. Latency prolongation was detected within 10 minutes of total, arterial, or venous ischemia. During the revascularization, both amplitude and latency improved, but not to the original values at the start. The results show that CMAP monitoring can provide easily detectable, objective indication of vascular compromise to a muscle graft within as early as 10 minutes of total, arterial, and venous ischemia. Changes in latency are more constant and predictable compared with amplitude changes. This method can provide continuous monitoring and can be used in buried muscle grafts.
Keywords: free muscle graft; ischemia; compound muscle action potential